Working towards a green job?: Autoworkers, climate change and the role of collective identity in union renewal. (September 2022) - Allan, Kori; Robinson, Joanna
This article examines the important, yet under-examined, issue of green workforce development and industrial relations and the role of unions and workers in shaping a transition to a green economy. Based on interviews with labour leaders and rank-and-file workers in the auto manufacturing sector in Ontario, Canada, this article interrogates how environmentalism and climate change potentially construct a sense of purpose among heterogenous union members, particularly in the context of decreasing union power, de-industrialization and neoliberalism. In order to understand how climate change can shape union purpose, we investigate how a diverse range of union members – beyond leaders – understand climate change and the appropriate strategies to address it and how this sustains or hinders collective identity within the union. We argue that understanding internal differences in collective identities is key for unions to start to rebuild power resources. Our research demonstrates that future union success and solidarity among workers might be dependent on the ability of unions to recognize and negotiate multiple collective identities. By incorporating innovations into the union, a more flexible and multi-dimensional collective identity regarding labour environmentalism could be built and sustained.